Organizational justice and disability pension from all-causes, depression and musculoskeletal diseases: A Finnish cohort study of public sector employees - Juvani, Anne; Oksanen, Tuula; Virtanen, Marianna; Elovainio, Marko; Salo, Paula; Pentti, Jaana; Kivimäki, Mika; Vahtera, Jussi (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'Work-related stress has been linked to increased risk of disability pensioning, but the association between perceived justice of managerial behavior and decision-making processes at the workplace (ie, organizational justice) and risk of disability pensioning remains unknown. We examined the associations of organizational justice and its relational and procedural components with all-cause and diagnosis-specific disability pensions with repeated measures of justice. ' ' METHODS ': 'Data from 24 895 employees responding to repeated surveys on organizational justice in 2000–2002 and 2004 were linked to the records of a national register for disability pensions from 2005–2011. Associations of long-term organizational justice (average score from two surveys) with disability pensions were studied with Cox proportional hazard regression adjusted for demographics, socioeconomic status, baseline health and health risk behavior, stratified by sex. ' ' RESULTS ': 'During a mean follow-up of 6.4 years, 1658 (7%) employees were granted disability pension (282 due to depression; 816 due to musculoskeletal diseases). Higher organizational justice was associated with a lower risk of disability pensioning [hazard ratio (HR) per one-unit increase in 5-point justice scale 0.87 (95% CI 0.81–0.94)]. For disability pension due to depression and musculoskeletal diseases, the corresponding HR were 0.77 (95% CI 0.65–0.91) and 0.87 (95% CI 0.79–0.97), respectively. Adjustment for job strain and effort–reward imbalance attenuated the HR by 20–80%. ' ' CONCLUSIONS ': 'Supervisors` fair treatment of employees and fair decision-making in the organizations are associated with a decreased risk of disability pensioning from all-causes, depression and musculoskeletal diseases. These associations may be attributable to a wider range of favorable work characteristics.
Keywords: depression; disability; disability pension; disability retirement; early exit; Finland; Finnish cohort study; musculoskeletal disease; organizational justice; psychosocial work environment; public sector employee; work stress